2020
DOI: 10.1111/mec.15719
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the phylogenetic diversity, primary habitats, and abundances of free‐living Symbiodiniaceae on a coral reef

Abstract: Dinoflagellates of the family Symbiodiniaceae are key primary producers in marine ecosystems (LaJeunesse et al., 2018). The Symbiodiniaceae evolved to live in symbiosis with numerous marine organisms from foraminifera to scleractinian corals (Carlos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 109 publications
(233 reference statements)
0
44
0
Order By: Relevance
“…Our findings indicate that obligate corallivore feces contain live Symbiodiniaceae cells at densities two to seven orders of magnitude higher than other environmental reservoirs, such as the water column, sediments and macroalgae (this work [22,35]), and up to three orders of magnitude higher than feces of the one other corallivorous fish that has been examined: the Caribbean parrotfish S. viride [14]. Corallivore feces that come in direct contact with live coral colonies are likely to facilitate the transmission of Symbiodiniaceae cells between colonies.…”
Section: Corallivores Promote the Dispersal Of Live Symbiodiniaceae Cmentioning
confidence: 59%
See 2 more Smart Citations
“…Our findings indicate that obligate corallivore feces contain live Symbiodiniaceae cells at densities two to seven orders of magnitude higher than other environmental reservoirs, such as the water column, sediments and macroalgae (this work [22,35]), and up to three orders of magnitude higher than feces of the one other corallivorous fish that has been examined: the Caribbean parrotfish S. viride [14]. Corallivore feces that come in direct contact with live coral colonies are likely to facilitate the transmission of Symbiodiniaceae cells between colonies.…”
Section: Corallivores Promote the Dispersal Of Live Symbiodiniaceae Cmentioning
confidence: 59%
“…However, the dispersal mechanisms that make Symbiodiniaceae cells available to prospective host corals have not been resolved (but see [15,45]), and Symbiodiniaceae cell densities in environmental reservoirs appear relatively low (sediments: 10 1 -10 3 cells ml − 1 ; seawater: 10 0 -10 1 cells ml − 1 ; macroalgae: 10 2 -10 3 cells ml − 1 , Fig. 1 [14,22,35]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ndings indicate that obligate corallivore feces contain live Symbiodiniaceae cells at densities two to seven orders of magnitude higher than other environmental reservoirs, such as the water column, sediments and macroalgae (this work; Fujise et al, 2021;Littman et al, 2008), and up to three orders of magnitude higher than feces of the one other corallivorous sh that has been examined: the Caribbean parrot sh S. viride (Castro-Sanguino and Sánchez, 2012). Corallivore feces that come in direct contact with live coral colonies are likely to facilitate the transmission of Symbiodiniaceae cells between colonies.…”
Section: Corallivores Promote the Dispersal Of Live Symbiodiniaceae Cmentioning
confidence: 60%
“…Approximately 75% of spawning and 10% of brooding coral species acquire their Symbiodiniaceae from the environment with each generation (Baird et al, 2009), and adult corals may take up environmental Symbiodiniaceae cells to replenish their microbiomes following abiotic stress (Boulotte et al, 2016;Lewis and Coffroth, 2004;Rouzé et al, 2019). However, the dispersal mechanisms that make Symbiodiniaceae cells available to prospective host corals have not been resolved (but see Coffroth et al, 2006;Nitschke et al, 2016), and Symbiodiniaceae cell densities in environmental reservoirs appear relatively low (sediments: 10 1 -10 3 cells ml -1 ; seawater: 10 0 -10 1 cells ml -1 ; macroalgae: 10 2 -10 3 cells ml -1 , Figure 1; Castro-Sanguino and Sánchez, 2012;Fujise et al, 2021;Littman et al, 2008) Cell densities reported in this study (all obligate corallivore and grazer/detritivore feces data and some data for facultative corallivore feces, sediments and seawater) represent live cell densities only, based on results from hemocytometry with the cell viability dye, trypan blue. Previously published cell densities for sediment and seawater (Fujise et al, 2021;Littman et al, 2008), macroalgae (Fujise et al, 2021), and facultative corallivore feces (Castro-Sanguino and Sánchez, 2012) may include both dead and live cells and were quanti ed using hemocytometry (Castro-Sanguino and Sánchez, 2012), a combination of ow-cytometry and hemocytometry (Littman et al, 2008), or quantitative PCR (Fujise et al, 2021).…”
Section: Introductionmentioning
confidence: 99%